Promotion of SOCS4 in the proliferation and migration of esophageal squamous cell cancer by ubiquitinating SHCBP1 through CRL5 - YING Jie; YANG Haifeng; GE Jianxin (Zhongguo linchuang yanjiu)
Objective To analyze the role of suppressor of cytokine signaling 4 (SOCS4) in the proliferation and migration of esophageal squamous cell carcinoma (ESCC) , and to explore the relationship between the Cullin-RING ubiquitin E3 ligase 5 (CRL5) and Shc1 SH2.domain binding protein (SHCBP1) . Methods The proliferation and migration of ESCC Eca-109 cells were detected by CCK8 assay, clone formation assay, scratch assay and transwell assay. Co-immunoprecipitation combined with mass spectrometry was used to detect proteins interacting with SOCS4. Results SOCS4 was highly expressed in ESCC (P＜0.01) and negatively correlated with prognosis (P=0.048) . High expression of SOCS4 promoted the proliferation and migration of ESCC Eca-109 cells (t=2.503,P=0.046) . SOCS4 interacted with CRL5 and SHCBP1 and promoted SHCBP1 ubiquitination (P＜0.001) . Knockdown of SHCBP1 inhibited the proliferation and migration of ESCC Eca-109 cells (Day2: F=7.903,P=0.005; Day3: F=11.569,P<0.001; Day4: F=3.894,P=0.043) . Knockdown of SHCBP1 reversed the promoting effect of SOCS4 on the proliferation and migration of ESCC Eca-109 cells (Day3: F=7.343,P=0.030). Conclusion Patients with high SOCS4 expression have poor prognosis. SOCS4 promotes the proliferation and migration of ESCC by ubiquitinating SHCBP1.